Indusdelta und Rann of Kutch - Wilhelmy, Herbert (ERDKUNDE, 1968)
On the basis of historical sources, morphologic observations and old maps, the author attempted a reconstruction of the Indus Delta since the time of Alexander the Great. Around 325 BC, the coastline ran a little south of the 25th Parallel i. e. 60-100 km further inland than today. At the time of the Arabian Conquest (711/712) Badin still lay on an open bay of the sea which, through silting has, since the 11th century, turned into the salt marsh of the Rann of Kutch. Around 1600, the delta reached the line Lahori Bandar-Shahbandar-Mughalbin. The most important changes in the map of 1770 compared to that of 1600 lay in the major shift to the right of the Indus below Hala (1758/59). The delta-channels have, since this time, undergone continuous changes which influenced the blossoming and decline of a number of port towns. The deep submarine canyon off the present-day Haidari Creek indicates that in the same area as today, a main arm of the Indus must have had its mouth in post-Pleistocene times. East of the Indus Delta on the edge of the Tharr, the south-flowing Hakra, which was an independent perennial river well into the 6th century BC, built up its own delta which now lies in the depths of the contemporary Rann of Kutch.